Coinoculation impact on plant growth promotion: a review and meta-analysis on coinoculation of rhizobia and plant growth-promoting bacilli in grain legumes - Kaschuk, Glaciela; Auler, André Carlos; Vieira, Crislaine Emidio; Dakora, Felix Dapore; Jaiswal, Sanjay K.; da Cruz, Sonia Purin (Brazilian journal of microbiology, 2022)
Coinoculation of symbiotic N 2 -fixing rhizobia and plant growth-promoting Bacillus on legume seeds can increase crop productivity. We collected highly resolved data on coinoculation of rhizobia and bacilli on 11 grain legume crops: chickpea, common bean, cowpea, faba bean, groundnut, lentil, mung bean, pea, pigeon pea, soybean, and urad bean to verify the magnitude of additive effects of coinoculation in relation to single inoculation of rhizobia on plant growth and yield of grain legumes. Coinoculation of rhizobia and bacilli on legume seeds and/or soil during sowing significantly increased nodulation, nitrogenase activity, plant N and P contents, and shoot and root biomass, as well as the grain yield of most grain legumes studied. There were however a few instances where coinoculation decreased plant growth parameters. Therefore, coinoculation of rhizobia and Bacillus has the potential to increase the growth and productivity of grain legumes, and can be recommended as an environmental-friendly agricultural practice for increased crop yields.